2019
DOI: 10.1038/s41598-019-42270-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends of polyphenolics and anthocyanins accumulation along ripening stages of wild edible fruits of Indian Himalayan region

Abstract: Wild fruits are important food resources that provide health promoting nutraceutical components, which vary with ripening stages. In present study, five wild edible fruits of Indian Himalayan Region i.e ., Myrica esculenta , Berberis asiatica , Rubus ellipticus , Pyracantha crenulata and Morus alba were examined for their nutraceutical potential at different ripening stages.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…What's more, avone and avonol biosynthesis and diterpenoid biosynthesis were relatively higher in the early stages while amino acids and linolenic acid metabolism were prominent in the later stages. It is in agreement with the ndings in R. ellipticus that the concentrations of polyphenolic compounds reached maximum in unripened stages S-1 and S-2, and then decreased signi cantly as the fruits proceeding towards maturation [58]. The phenols are produced by plants for defensive purposes as "natural pesticides" and then would be oxidized and switch to anthocyanins biosynthesis for fruits maturation [32,35,38].…”
Section: Discussionsupporting
confidence: 90%
“…What's more, avone and avonol biosynthesis and diterpenoid biosynthesis were relatively higher in the early stages while amino acids and linolenic acid metabolism were prominent in the later stages. It is in agreement with the ndings in R. ellipticus that the concentrations of polyphenolic compounds reached maximum in unripened stages S-1 and S-2, and then decreased signi cantly as the fruits proceeding towards maturation [58]. The phenols are produced by plants for defensive purposes as "natural pesticides" and then would be oxidized and switch to anthocyanins biosynthesis for fruits maturation [32,35,38].…”
Section: Discussionsupporting
confidence: 90%
“…In general, the red matured stage displayed a higher level of TP than the green stage [19]. Earlier reports suggested that ripening of fruits and vegetable is associated with the significant accumulation of TP [38].…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in the polyphenol content with fruit ripening occurred in numerous species such as pomegranate [46], banana [47], some wild edible fruit [48], guava fruit [49], blueberry fruits [50], and olive drupe [51]. For the species Myrtus communis [44], a decrease in the total polyphenols of the fruits was characterized by ripening, showing a high intraspecific variability.…”
Section: Chemical Analysismentioning
confidence: 99%